The Role of Digital Competencies, AI, and Informal Learning in Enhancing Functional Skills: A Study of Islamic School Teachers in Southern Pakistan - Majeed, Muhammad Kashif; Ahmad, Tunku Badariah (International Journal of Religious and Interdisciplinary Studies, 2025)
This study examines the interplay between digital competencies, AI usage, and digital informal learning in enhancing functional skills among Islamic secondary school teachers in Southern Pakistan, a context underexplored in existing literature. Despite the global emphasis on technology-driven education, little is known about how these factors collectively influence teacher development in resource-constrained, culturally specific settings like Islamic schools in Muzaffargarh. Using a quantitative approach, data were collected via Google Forms from 450 teachers and analyzed with SPSS (v22) to address two research questions: (1) the impact of digital competencies on functional skills acquisition, moderated by AI tools, and (2) the role of AI-based informal learning in teaching effectiveness and skill development. Results revealed that while digital competencies alone did not significantly improve functional skills (p=0.067), AI tools demonstrated a strong moderating effect (p=0.000), enhancing teachers' ability to leverage digital resources. Additionally, AI-powered informal learning platforms positively influenced teaching adaptability and skill progression. The study contributes to theory by highlighting AI's pivotal role as a bridge between digital literacy and functional skills in non-Western educational contexts. Practically, it underscores the need for targeted teacher training programs integrating AI tools and digital informal learning alongside infrastructure investments. These findings offer policymakers and educators a framework to design contextually relevant professional development initiatives, addressing gaps in Pakistan's Islamic education system while informing similar global contexts undergoing digital transition.